Pembangunan dalam Perspektik Ekonomi Islam - Agung Eko Purwana (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2013)
Economic development is one of the strategies to achieve the goals that this nation aspires to. Economic growth, per capita income of the population, unemployment, poverty, and the balance of payments are measures achieved in assessing the success rate of economic development. But in realityHowever, in reality, the development that has been carried out has not produced optimal resultsoptimal results because it is still not in favor of many people.The increase in poverty and unemployment that is currently occurring, ultimately requires all parties to reformulate the appropriate development strategy to be applied in this country. So that there are no more people who are neglected. Economic, social and political experts have begun to conduct many studies on how to make development successful without being haunted by poverty and unemployment. The interesting thing in these studies comes from Muslim scholars and economists. They offer new alternatives along with the emergence of new theories of Islamic economics. Islamic economics, which is based on the teachings of Islamic shari'ah, does require its adherents to act professionally in the process of displaying neatness, truth, order, and order. Departing from the above explanation, this paper wants to examine how the Islamic economic perspective on development can solve the problems of poverty, unemployment, and equity.